Sports-related injuries sustained by officers of the State Fire Service on duty – nationwide 7-year follow-up - Dudziński, Łukasz; Panczyk, Mariusz; Kubiak, Tomasz; Milczarczyk, Tomasz (Frontiers in Public Health, 2023)
The accident rate in the State Fire Service from 2015 to 2021 related to sports activities was analyzed in relation to the regions of the country per year.The study included analysis of data from the SFS Headquarters -Department for Occupational Health and Safety and Preventive Health. Data collected from across the country in the form of an annual analysis of the accident. The reports included such information as: the number of accidents, the cause and circumstances of accident (injury), with a breakdown listing individual and group accidents.During the observation period, about 30,000 officers were on duty in the SFS, of which about 20% were on daily (8-hour) duty, and 80% were on shift (24-hour) duty. Between 2015 and 2021, there were N=11332 (Mean: 1617.4; SD: 284.1) accidents in SFS. Total accident covers individual and mass accidents. The number of sports injuries was N=4254 (Mean: 532.2; SD: 137.9).There is a need for comprehensive approach to physical training in the firefighter population. Physical activity should be continuous and systematic strengthening of the whole body. Sports activities should begin with performing thorough warm-ups. It is necessary to maintain facilities, premises, equipment and technical devices in a condition that sets the ground for doing sports safely and in a hygienic manner. Most of the sports injuries sustained by firefighters are related to team sports.